IMPLEMENTASI PENDIDIKAN KARAKTER KURIKULUM 2013 DI SMK BATIK 1 SURAKARTA - Djumali Djumali; Erlina Wijayanti (Jurnal Pendidikan Ilmu Sosial, 2018)
The purpose of this research are; (1) Implementation of curriculum 2013 on economics subjects in SMK Batik 1 Surakarta academic year 2017/2018; (2) Implementation of character education curriculum 2013 on economic subjects in SMK Batik 1 Surakarta academic year 2017/2018. The type of research used is qualitative. Subjects in this study Principal, Deputy head of curriculum, Economics teacher, and student. Data collection techniques used in this study are interviews, observation, and documentation. Data analysis techniques through data reduction, data presentation, and conclusions.The results of this research are: Implementation of character education curriculum 2013 on economic subjects in SMK Batik 1 Surakarta has been running well, this is evidenced based on their daily attitude that can already be said to have good character.